Transaction costs and dispute resolution: An economic approach to litigation and mediation - Sahata Eddy P Situmorang (PT WIM Solusi Prima, 2026)
This paper examines the concept of transaction costs in legal dispute resolution through the law and economics framework developed by Richard A. Posner. Posner argues that litigation and mediation can be rationally analyzed through cost-benefit calculations, with efficiency as the primary orientation. However, this approach cannot be mechanically applied in Indonesia's context, which has its own constitutional foundation and Pancasila values. This study employs a normative-comparative method with conceptual and comparative approaches. The findings indicate that Posner's transaction cost analysis has diagnostic value for identifying judicial inefficiency, but must be integrated with the principles of substantive justice, national sovereignty, and deliberative values that form the spirit of Indonesia's legal system. The proposed synthesis is a deliberation-based mediation that is simultaneously efficient and civilized.